Examining The Veracity Or Otherwise Of Woodrow Wilson’s Theory Of Politics-Administrative Dichotomy In Contemporary Nigeria’s Public Sector Management - Okoh, Itebite (Journal of Governance and Administrative Reform, 2025)
Abstract Woodrow Wilson’s idealized conception of the politics administration dichotomy continues to prove challenging in the context of Nigeria’s public sector. The persistent blurring of boundaries between political and administrative functions has contributed to systemic issues, including politicization, inefficiency, inter institutional conflict, and suboptimal service delivery. This study seeks to identify key points of intersection between political and administrative domains within Nigeria’s public institutions and to propose strategic approaches for their effective coexistence, thereby enhancing service quality, institutional efficiency, accountability, and transparency. Anchored in public choice theory which conceptualizes political and bureaucratic actors as rational, self-interested individuals the study adopts an emic ontological perspective consistent with qualitative research paradigms. Secondary qualitative data were obtained from a variety of sources, including online newspapers, reports from anti-corruption agencies and non governmental organizations (NGOs), academic monographs, and peer-reviewed journal articles. These data were systematically analyzed using content analysis techniques. The findings demonstrate a significant degree of politicization across Ministries, Departments, and Agencies (MDAs), notably in areas such as financial and budgetary administration, recruitment, appointment, promotion, project execution, disciplinary procedures, and policy development. These dynamics undermine the classical distinction between politics and administration originally posited by Wilson. This study contends that a functional synergy between both spheres is attainable through targeted reforms. Recommended measures include strengthening merit-based recruitment and promotion processes to foster professionalism, enforcing ethical standards to safeguard institutional integrity, and cultivating collaborative relationships between political and administrative actors rooted in a shared commitment to public service. To mitigate the limitations of the current methodology, future research should incorporate interviews or adopt mixed method approaches. Comparative analyses across diverse administrative systems are also encouraged to deepen understanding of the complexities surrounding the politics administration dichotomy. Keywords: politics; public administration; administrative dichotomy; governance   Abstrak Konsepsi Woodrow Wilson mengenai dikotomi politik–administrasi terus menjadi tantangan dalam konteks sektor publik di Nigeria. Kaburnya batas antara fungsi politik dan administrasi telah berkontribusi terhadap berbagai permasalahan sistemik, termasuk politisasi, inefisiensi, konflik antar lembaga, serta rendahnya kualitas layanan publik. Studi ini bertujuan untuk mengidentifikasi titik-titik persinggungan utama antara ranah politik dan administrasi dalam institusi publik Nigeria, serta mengusulkan pendekatan strategis untuk memastikan koeksistensi yang efektif di antara keduanya, guna meningkatkan kualitas layanan, efisiensi kelembagaan, akuntabilitas, dan transparansi. Berlandaskan pada teori pilihan publik yang memandang aktor politik dan birokrasi sebagai individu rasional yang berorientasi pada kepentingan diri sendiri. penelitian ini mengadopsi perspektif ontologis emik yang sejalan dengan paradigma penelitian kualitatif. Data kualitatif sekunder dikumpulkan dari berbagai sumber, termasuk surat kabar daring, laporan lembaga antikorupsi dan organisasi non pemerintah (NGO), monograf akademik, serta artikel jurnal ilmiah terindeks. Seluruh data dianalisis secara sistematis menggunakan teknik analisis isi. Temuan menunjukkan tingkat politisasi yang tinggi di berbagai Kementerian, Departemen, dan Lembaga (KDL), khususnya dalam aspek pengelolaan keuangan dan anggaran, rekrutmen, pengangkatan, promosi, pelaksanaan proyek, prosedur disipliner, serta perumusan kebijakan. Dinamika ini merusak pemisahan teoretis antara politik dan administrasi sebagaimana yang dikemukakan oleh Wilson. Penelitian ini berargumen bahwa sinergi fungsional antara kedua ranah tersebut dapat dicapai melalui reformasi yang terarah. Rekomendasi mencakup penguatan sistem berbasis merit dalam proses rekrutmen dan promosi untuk mendorong profesionalisme, penegakan standar etika untuk menjaga integritas kelembagaan, serta pengembangan hubungan kolaboratif antara aktor politik dan administratif yang dilandasi komitmen bersama terhadap pelayanan publik. Untuk mengatasi keterbatasan metodologi saat ini, penelitian lanjutan disarankan untuk mengintegrasikan wawancara atau pendekatan metode campuran. Analisis perbandingan lintas sistem administrasi juga dianjurkan untuk memperdalam pemahaman terhadap kompleksitas dikotomi politik administrasi. Kata kunci: politik; administrasi publik; dikotomi administratif; tata kelola